31. INITIAL EVALUATION OF THE RERULTS OF LAPAROSCOPIC SURGERY TO PLACE EXTRAPERITONEAL ARTIFICIAL MESH FOR INGUINAL HERNIA TREATMENT ON PATIENTS WITH OLD INCISIONS OVER HYPOGASTRIC REGION (Vietnam Journal of Community Medicine, 2024)
Background: Inguinal hernia is a disease in which abdominal organs protrude through the inguinal canal or through the natural weakness of the abdominal wall above the inguinal fold under the skin or into the scrotum and this is a quite common disease. Laparoscopic surgery has been considered one of the first choice methods in treating inguinal hernia. However, with this technique, for patients with old surgical scars in the abdomen, creating a cavity to place the mesh poses a big challenge for the surgeon.Objective: To determine the rate of accidents, complications and success rate of laparoscopic surgery to place artificial mesh in front of the peritoneum to treat inguinal hernia with old incisions in the abdomen below the navel. Research method: Descriptive study of a series of cases.Research results: During the 4-year study period from January 1, 2020 to September 30, 2023 with 21 patients studied, we recorded the following results :1. Clinical and subclinical characteristics: average age was 56.57 ± 19.74 (youngest age was 25, oldest age was 85), male 95.2%, female 4.8%. There were 47.6% of cases with a history of laparoscopic surgery and 47.6% of cases with open surgery in the abdominal area below the navel. There was 1 case with both laparoscopic and open surgery scars; Most herniated organs were indirect inguinal hernias 71.4%, direct 19.0% and both direct and indirect 9.5%. The shortest surgery time was 40 minutes, the longest surgery time was 180 minutes, the average surgery time was 81.67 ± 31.95 minutes.2. The rate of complications during surgery was 42.9%, complications after surgery was 9.5%.3. The success rate of laparoscopic surgery to place artificial mesh in front of the peritoneum in patients with old incisions in the abdomen below the navel was 90.5%.Conclusion: Laparoscopic surgery to place artificial mesh in front of the peritoneum in patients with old surgical scars in the lower abdomen is safe and effective, the postoperative course has many advantages and disadvantages similar to laparoscopic surgery to treat of common inguinal hernia (TEP).
Keywords: Inguinal hernia, laparoscopic inguinal hernia, old surgical wound, TEP.